Computer-Aided Diagnosis Evaluation of the Correlation Between Magnetic Resonance Imaging With Molecular Subtypes in Breast Cancer - Meng, Wei; Sun, Yunfeng; Qian, Haibin; Chen, Xiaodan; Yu, Qiujie; Abiyasi, Nanding; Yan, Shaolei; Peng, Haiyong; Zhang, Hongxia; Zhang, Xiushi (Frontiers in Oncology, 2021)
Background There is a demand for additional alternative methods that can allow the dif-ferentiation of the breast tumor into molecular subtypes precisely and conveniently. Purpose The present study aimed to determine suitable optimal classifiers and investigate the general applicability of computer-aided diagnosis (CAD) to associate between the breast cancer molecular subtype and the extracted MR imaging features. Methods We analyzed a total of 264 patients (mean age: 47.9 ± 9.7 years; range: 19–81 years) with 264 masses (mean size 28.6 ± 15.86mm, range 5-91 mm) using a Unet model and Gradient Tree Boosting for segmentation and classification. Results The tumors were segmented clearly by the Unet model automatically. All the ex-tracted features which including the shape features ,the texture features of the tumors and the clinical features were input into the classifiers for classification, and the results showed that the GTB classifier is superior to other classifiers, which achieved F1-Score 0.72, AUC 0.81 and score 0.71. Analyzed the different features combinations, we founded that the texture features associated with the clinical features are the optimal features to different the breast cancer subtypes. Conclusion CAD is feasible to differentiate the breast cancer subtypes , automatical segmentation were feasible by Unet model and the extracted texture features from breast MR imaging with the clinical features can be used to help differentiating the molecular subtype. Moreover, in the clinical features, BPE and age characteristics have the best potential for subtype.